The Main Issues and Perspectives of The Administrative and Legal Regulation of The Higher Education Reform in Ukraine - Levchenko, Kateryna; Lehenkyi, Mykola; Bondarchuk, Serhiy; Borodin, Yevheniy; Shved, Olha (My University, 2020)
This article explicates the relevance of the higher education reform in Ukraine in order to achieve its compliance with the European and world educational standards. It also characterizes the importance and key tasks of the legal and administrative support of such reform. The generalizations of the researches carried out in the specified sphere are also studied. It notes the importance of ensuring non-discriminative access to educational services by applicants with special educational needs as an important aspect of protecting their rights and freedoms as a key requirement of the Bologna Process. Based on an analysis of innovative methods of the administrative activity in the article, the urgency of forming the state-public form of management of higher education is defined. It analyses the current regulatory and legal support for the management of higher education, as well as the introduction of the institution of educational ombudsman principles of the relevant state educational policy. It aims to supplement and improve the legal acts in order to ensure democracy, transparency and the inclusion of elements of corporate governance. The problems of regulating the activities of the National Higher Education Quality Assurance Agency were noted, and proposals were made to address them. The most pressing problems of research of the processes of higher education reform, which require an appropriate legal regulation, are identified. Among them are: ensuring the protection of the rights and freedoms of participants in the higher education process including gender equality, systemic restructuring of management model of higher education; and improving procedures related to ensuring the educational services’ quality.
Keywords: higher education; administrative and legal regulation; human rights and gender equality; educational services quality